STARETEGI PEMBELAJARAN PAI PADA PTAI - Dr. Mardyawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2016)
Purpose of Education at very influential in the implementation, dynamics, direction and implementation of education at a higher education, especially at the College of Islamic Religion (PTAI). Thus it is necessary PTAI depth critical evaluation, for the formulation and the concept is very determining educational goals of the institution's goals. In the end, the quality or the quality of the education is the foundation of conceptual philosophy of education which frees and able to prepare future generations to survive (survive) and successfully face the challenges of his time. The ultimate goal of learning a particular college is scored undergraduate PTAI skilled in the art that characterized and, coupled with the values ​​of Islam. These objectives would be achieved by managing the learning process in PTAI and one way to achieve that goal is to pack the lecture by incorporating the material into an Islamic education curriculum in PTAI. Thus, the learning process is not just a professor presenting lectures (courses) to students who menghusus in each department, but deliver the lecture material makes matter the religion of Islam as one of the basic theory in presenting the material. Students are no longer made passive but should be made the driving force of educational activities (generators). Given the purpose of education in the College of Islamic Religion which prepares students to be scholars who